Implementing standards-based mathematics instruction : a casebook for professional development - Stein, Mary Kay.; National Council of Teachers of Mathematics (New York : Teachers College Press, 2000)
Presents case studies of eight math teachers' instructional methods, focusing on how students and teachers undertake specific mathematical tasks in the classroom.
"National Council of Teachers of Mathematics.".
Includes bibliographical references (p. 137-139) and index.
Professional
Keywords: Mathematics -- Study and teaching (Middle school) -- Case studies; Mathematics -- Study and teaching -- Case studies